2008
DOI: 10.1097/ta.0b013e31815dd4c4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Telemedicine Upon Rural Trauma Care

Abstract: Telemedicine significantly improved rural LCH evaluation and management of trauma patients. More severely injured trauma patients were identified and more rapidly transferred to the TC. Total TC hospital costs were significantly decreased without significant changes in TC mortality. Introduction of telemedicine consultation to rural LCH emergency departments expanded LCH trauma capabilities and conserved TC resources, which were directed to more severely injured patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(127 citation statements)
references
References 23 publications
3
121
1
2
Order By: Relevance
“…While studies on telehealth in emergency departments tend to be conducted by researchers associated with tele emergency care programs, the results from these studies are generally positive (Blanchet, 2008;Doheny-Farina et al, 2003;Duchesne et al, 2008;Latifi et al, 2007;Ricci et al, 2003;Rogers et al, 2001;Sorondo, Holmberg, & Bjorn, 2011).…”
Section: Literature On Two Emerging Uses: Telepharmacy and Tele-emergmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies on telehealth in emergency departments tend to be conducted by researchers associated with tele emergency care programs, the results from these studies are generally positive (Blanchet, 2008;Doheny-Farina et al, 2003;Duchesne et al, 2008;Latifi et al, 2007;Ricci et al, 2003;Rogers et al, 2001;Sorondo, Holmberg, & Bjorn, 2011).…”
Section: Literature On Two Emerging Uses: Telepharmacy and Tele-emergmentioning
confidence: 99%
“…Duchesne and colleagues examined the impact of telehealth on trauma care provided at seven rural hospital emergency departments in Mississippi (Duchesne et al, 2008). The study sample included over 800 traumatically-injured patients presented to the participating hospital emergency departments between January 2000 and January 2005.…”
Section: Literature On Two Emerging Uses: Telepharmacy and Tele-emergmentioning
confidence: 99%
“…Additionally, providing structured feedback to providers based on patients transferred from their institutions brings an educational opportunity to every practice encounter. 4 Taken together, telemedicine with real-time consultation and remote learning opportunities might very well improve trauma care in rural settings. 5 Our survey had several potential limitations.…”
Section: Education and Support In Practicementioning
confidence: 99%
“…Lastly, this study is consistent with previous research which has demonstrated that specialty telemedicine consultations can result in improved patient safety. 18,[39][40][41][42][43][44] …”
Section: Discussionmentioning
confidence: 99%